6.01.001-B: Newfoundland and Labrador Folk Festival, 1978 - Conception Bay Arts Association (1978)
Clarification: the Conception Bay Arts Association, organizers of the annual Conception Bay Folk Festival in Carbonear, decided to celebrate the tenth anniversary of that event by hosting the annual Newfoundland and Labrador Folk Festival, usually held in St. John's. It is this provincial event to which the book refers. (inside cover - p. 1)